2001
DOI: 10.1093/oxfordjournals.molbev.a003795
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of Human DNA Sequence Variation in a 10-kb Region on Chromosome 1

Abstract: Human DNA variation is currently a subject of intense research because of its importance for studying human origins, evolution, and demographic history and for association studies of complex diseases. A approximately 10-kb region on chromosome 1, which contains only four small exons (each <155 bp), was sequenced for 61 humans (20 Africans, 20 Asians, and 21 Europeans) and for 1 chimpanzee, 1 gorilla, and 1 orangutan. We found 52 polymorphic sites among the 122 human sequences and 382 variant sites among the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
65
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(79 citation statements)
references
References 24 publications
13
65
0
1
Order By: Relevance
“…This point estimator of the mutation rate is lower, though not significantly different, than values observed for other autosomal loci. 20,21 Among the populations studied, the African populations have higher levels of diversity compared to nonAfrican populations, with West Africans having the highest level of diversity and Europeans having the lowest level of diversity (Tables 1 and 2). Across all the Figure 1 Genomic structure of the IL13 gene and distribution of SNPs identified in this study.…”
Section: Resultsmentioning
confidence: 95%
“…This point estimator of the mutation rate is lower, though not significantly different, than values observed for other autosomal loci. 20,21 Among the populations studied, the African populations have higher levels of diversity compared to nonAfrican populations, with West Africans having the highest level of diversity and Europeans having the lowest level of diversity (Tables 1 and 2). Across all the Figure 1 Genomic structure of the IL13 gene and distribution of SNPs identified in this study.…”
Section: Resultsmentioning
confidence: 95%
“…Loci from some other species of nematodes also demonstrate diversity at nuclear loci as high as the $10% seen in C. remanei, such as b-tubulin in Haemonchus contortus (Beech et al 1994) and ITS1-rDNA of Longidorus biformis (Ye et al 2004), although most reports indicate levels of silent-site diversity of #2% (Anderson et al 1998;Cutter et al 2006). Similarly high levels of nucleotide polymorphism have also been reported in several species of mycophagous Drosophila Shoemaker et al 2004), suggesting that intraspecific per-nucleotide diversities of 5-10% may not be unusual in a variety of taxa, in spite of the predominent view of low-to-moderate levels of genetic variation within genetic model organisms: Drosophila melanogaster p si $ 1.6% (Andolfatto 2001), Arabidopsis thaliana u si $ 1.6%, maize u si $ 1.5% (Wright and Gaut 2005), and human p si $ 0.08% (Zhang 2000;Yu et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we find that the analyses of pseudogenes (Li and Tanimura 1987;Nachman and Crowell 2000;Martinez-Arias et al 2001) and introns (Bergstrom et al 1999;Chen et al 2001) have produced much lower estimates of evolutionary divergence than those observed in synonymous sites in protein coding genes (Li and Tanimura 1987;Wolfe et al 1989;Easteal 1991;Keightley and Eyre-Walker 2000;Duret et al 2002;Kumar and Subramanian 2002). Also, intergenic DNA (excluding regulatory sites), which is expected to mutate at a rate similar to that for the coding DNA, also consistently shows much smaller evolutionary divergences than those obtained from coding sequences (Bohossian et al 2000;Zhao et al 2000;Chen et al 2001;Mathews et al 2001;Yu et al 2001). This observation is not a random chance occurrence due to paucity of data, because these studies have involved direct comparisons of long intergenic regions (Bohossian et al 2000;Zhao et al 2000;Chen et al 2001) and relatively large numbers of coding genes (Wolfe et al 1989;Keightley and Eyre-Walker 2000;Duret et al 2002;Kumar and Subramanian 2002).…”
mentioning
confidence: 97%